How narratives shape policy: Lessons learned from port projects adjacent to coral reefs in Florida and the Cayman Islands. (October 2022) - Bailey, Sabine; Dunning, Kelly Heber; Morris, Daniel; Williamson, Ryan D.
Abstract: Coral reefs hold immense economic, ecological, and cultural value but are severely threatened by climate change and other local stressors, such as coastal development projects. In Miami, Florida and the Cayman Islands, two locations with vibrant coral reef ecosystems, large scale dredging port projects have either been planned or implemented. Environmental disputes emerged during both projects due to the uncertainty over ecological risks of dredging on coral ecosystems. In this research, a refined version of the Narrative Policy Framework is employed to understand how narratives used by stakeholders, both supportive of and opposed to these dredging projects, influenced the ultimate implementation status and impacts therein. The findings show that supporters of the port projects place themselves as heroes in their narratives, in which they advocate for economic prosperity while simultaneously presenting their side as protecting the environment through actions with high technological certainty. On the other hand, opponents of the port projects emphasize the environmental risks involved by contesting the science presented. Opponents portray supporters as villainous for potential dredging impacts and for overstating technological certainty. Across the cases, this paper finds the heterogeneity and dynamism in the use of science and symbols cannot be predicted by supporters or opponents of the projects but rather, are adaptable to either cause readily. As environmental disputes increase along with the impacts of climate change, understanding the narratives that coalitions of stakeholders employ to advocate for preferred policies will be important for global environmental policy-makers. Highlights: Narratives are important during environmental disputes over vulnerable ecosystems. Narratives about constitutional rights, science, risks, and economics are powerful. Narratives made by supporters of port projects emphasized economic benefits. Opponents of port projects used science in their narratives more than supporters. Narratives made by opponents of port projects led to the delays of port projects.